2022 Physics Education Research Conference Proceedings 2022
DOI: 10.1119/perc.2022.pr.li
|View full text |Cite
|
Sign up to set email alerts
|

How inclusiveness of learning environment predicts female and male students� physics grades and motivational beliefs in introductory physics courses

Abstract: In this study, we adapted a prior identity framework to investigate how students' perception of the inclusiveness of the learning environment (including sense of belonging, peer interaction and perceived recognition) in an introductory physics course predicts their course grades and physics motivational beliefs (including self-efficacy, interest and identity) at the end of this course. We found signatures of inequitable and non-inclusive learning environment in that female students' mean scores for sense of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Prior studies have shown that students' sense of belonging plays an important role in their persistence and retention in physics, particularly for students from historically marginalized groups in this field [16,17]. Additionally, earlier studies have indicated that sense of belonging is a critical component of students' perception of the inclusiveness of the learning environment, predicting both their psychological and academic outcomes in physics courses [18][19][20]. For example, sense of belonging has been shown to directly predict students' physics self-efficacy and interest, as well as their performance in physics conceptual inventories and course grades [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that students' sense of belonging plays an important role in their persistence and retention in physics, particularly for students from historically marginalized groups in this field [16,17]. Additionally, earlier studies have indicated that sense of belonging is a critical component of students' perception of the inclusiveness of the learning environment, predicting both their psychological and academic outcomes in physics courses [18][19][20]. For example, sense of belonging has been shown to directly predict students' physics self-efficacy and interest, as well as their performance in physics conceptual inventories and course grades [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, earlier studies have indicated that sense of belonging is a critical component of students' perception of the inclusiveness of the learning environment, predicting both their psychological and academic outcomes in physics courses [18][19][20]. For example, sense of belonging has been shown to directly predict students' physics self-efficacy and interest, as well as their performance in physics conceptual inventories and course grades [18][19][20][21][22]. Various factors have been identified as influencing students' sense of belonging in physics courses, including their interactions with instructors and peers, the presence of role models, and the prevalence of stereotypes in the field [23].…”
Section: Introductionmentioning
confidence: 99%